Does women’s mobile phone ownership matter for health? Evidence from 15 countries - LeFevre, Amnesty E; Shah, Neha; Bashingwa, Jean Juste Harrisson; George, Asha S; Mohan, Diwakar (BMJ global health, 2020)
Mobile phones have the potential to increase access to health information, improve patient–provider communication, and influence the content and quality of health services received. Evidence on the gender gap in ownership of mobile phones is limited, and efforts to link phone ownership among women to care-seeking and practices for reproductive maternal newborn and child health (RMNCH) have yet to be made. This analysis aims to assess household and women’s access to phones and its effects on RMNCH health outcomes in 15 countries for which Demographic and Health Surveys data on phone ownership are available. Multilevel logistic regression models were used to explore factors associated with women’s phone ownership, along with the association of phone ownership to a wide range of RMNCH indicators. Study findings suggest that (1) gender gaps in mobile phone ownership vary, but they can be substantial, with less than half of women owning mobile phones in several countries; (2) the gender gap in phone ownership is larger for rural and poorer women; (3) women’s phone ownership is generally associated with better RMNCH indicators; (4) among women phone owners, utilisation of RMNCH care-seeking and practices differs based on their income status; and (5) more could be done to unleash the potential of mobile phones on women’s health if data gaps and varied metrics are addressed. Findings reinforce the notion that without addressing the gender gap in phone ownership, digital health programmes may be at risk of worsening existing health inequities.